Evaluating Teaching Strategies in Higher Education from Students’ Perspectives - Amani K Alghamdi; Fatma Kayan; Abdulghanni Hattami (Journal of Education and Learning (EduLearn), 2017)
This study was conducted to investigate students’ perception of learning experiences at one of the largest government universities in the eastern province of Saudi Arabia. The sample consisted of male and female students and their instructors enrolled in four main colleges (Arts, Education, Preparatory year, and Science). Data were collected through a survey and focus group interviews during the fall semester of 2014-2015 academic year. The results provide feedback to faculty members about the quality of content, format, and structure of their courses, and can contribute to teaching and learning processes by facilitating faculty growth, development, and self-improvement.